A Study On Malaysian Households’ Purchase Intention Of Water Purifier - Nadarajan, Nedumaaran (2014)
Drinking water quality has been one of the main concerns of Malaysian households today. Despite government’s continuous efforts to improve water quality, concerned households are installing domestic water purifiers at their own cost for added peace of mind. However, why households acted to purchase water purifiers is still not fully understood. The main aim of this investigation is to identify factors that influence Malaysian households’ purchase intention of water purifier. Cognitive, affective and behavioural or the CAB model is used to examine factors that influence Malaysian households purchase intention of water purifier.